An Empirical Evaluation of Transfer-of-Training of Two Flight Simulation Games. (February 2017) - Korteling, Hans J. E.; Helsdingen, Anne S.; Sluimer, Ralf R.
Aim . The objective of this study was to collect evidence of transfer-of-training to professional performance provided by two stand-alone PC-based flight games. Background . These realistic games, Falcon 4.0 (F-16 specific) and Microsoft Flight Simulator (civil aircraft), are designed for entertainment purposes, lacking any purposeful or explicit instructional support. Method . This quasi-experimental study used three pre-existing groups of gamers (n = 37; Falcon 4.0 gamers, Microsoft Flight Simulator gamers and control group: gamers without flight game experience) that performed three typical F-16 flight tasks in a high-fidelity fixed-base flight simulator. Results . The Falcon 4.0 gamers performed substantially better on almost all tasks compared to the control group, and to a lesser degree to Microsoft Flight Simulator gamers. The Falcon 4.0 group showed near- and far-transfer on almost all flight performance measures: the game had prepared them for the generic and specific military aspects of the test flight tasks. Performance of the Microsoft Flight Simulator gamers indicated only far-transfer, i.e., transfer of more generic flight skills from the game to the test flight tasks. Conclusion . Both near- and far-transfer of job related competences may occur by playing realistic entertainment games.